Hubungan Antara BUMD dan Koneksi Politik di Indonesia: Suatu Telaah Pustaka - DD Amdanata; Burhan (Bulletin of Management and Business, 2021)
This article aims to reveal the relationship between Regional Owned Enterprises (BUMD) and political connections in the regions. BUMD was formed with clear objectives, one of which is to become a source of Regional Original Income (PAD). However, in practice, BUMD's activities are heavily influenced by external factors that make BUMD's performance worse. One of the external factors is the political power in an area. This article is a theoretical concept that will reveal the relationship between BUMD and political connections through a literature review. The research method used is qualitative. The conclusion of the study shows that regional political connections have a negative influence on company performance.